Association of late-life changes in blood pressure and cognitive status - Lacruz, Maria Elena; Tiller, Daniel; Kluttig, Alexander; Greiser, Karin Halina; Nuding, Sebastian; Werdan, Karl; Haerting, Johannes (Journal of geriatric cardiology, 2016)
Disagreement exists on the association between changes in blood pressure and cognitive impairment. We aimed to examine whether 4-year changes in systolic and diastolic blood pressure (SBP and DBP) are associated with cognitive status in a representative sample of older men and women.